Synthesis of Crosslinked 2′‐OMe RNA Duplexes Using 2‐Amino‐6‐Vinylpurine and Their Application for Effective Inhibition of miRNA Function. Issue 3 (22nd March 2022) - Abdelhady, Ahmed Mostafa; Hirano, Yu; Onizuka, Kazumitsu; Okamura, Hidenori; Komatsu, Yasuo; Nagatsugi, Fumi
Abstract: Crosslinking reactions to nucleic acids are an effective way to prepare stable complexes formed by covalent bonding. We demonstrated that fully 2′‐ O ‐methylated (2′‐OMe) RNAs having a 2‐amino‐6‐vinylpurine (AVP) exhibited an efficient crosslinking to uracil in the target RNA. Recently, we reported the preparation of crosslinked 2′‐OMe RNA duplexes using AVP and the anti‐miRNA oligonucleotides (AMOs) containing crosslinked duplexes at the terminal positions. These AMOs exhibited efficient microRNA (miRNA) inhibition at very low concentrations. In this article, we describe the chemical synthesis of 2′‐OMe oligonucleotides containing AVP and preparation of the AMOs bearing crosslinked 2′‐OMe RNA duplexes using AVP. In addition, we describe in detail the miRNA inhibition assay using these AMOs. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of phosphoramidite of 2‐amino‐6‐vinylguanosine derivative Basic Protocol 2 : Synthesis of AVP‐2′‐OMe RNA Basic Protocol 3 : Evaluation of the crosslink reactivity of CFO containing AVP to the 2′‐OMe RNA and preparation of AMOs containing crosslinked duplex Basic Protocol 4 : miRNA inhibition assays